Government for the People : On the Determinants of the Size of U.S. Government - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 2007)
Trends in the size of U.S. government are examined. In the postwar period, general government primary spending rose by u percent of GDP a year through 1975, stabilizing thereafter. With higher social transfers offset by a lower burden of defense spending, expansion reflected a baby-boom driven rise in education spending. The parallel improvement in tax efficiency helped equate the benefits of higher spending with the costs from higher taxation, in accordance with a marginalist view of the size of government. Looking forward, the retirement of baby boomers appears likely to expand government and lead to a more efficient tax system.